Analisis Implementasi PSAK 71 Terhadap Cadangan Kerugian Penurunan Nilai (Studi Kasus Pada PT Bank XYZ Tbk) - Rahayu, Duwi (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2021)
Abstract PSAK 71 is officially effective in 2020, banking issuers are required to include the formation of CKPN. The purpose of this study is to determine the analysis of the implementation of PSAK 71 against the allowance for impairment losses at PT. Bank XYZ Tbk. The data analysis of this research was carried out from 2017 to 2019, because PT. Bank XYZ Tbk has implemented PSAK 71 from an early age in 2017. The method used in this research is descriptive qualitative. The results of this study are the determination of CKPN, recognition and measurement of CKPN PT. Bank XYZ Tbk is in compliance with PSAK 71. Where PT. Bank XYZ Tbk recognizes and measures allowance for losses for financial instruments totaling ECL - 12 months if credit risk is low and there is no significant increase. On the other hand, PT. Bank XYZ Tbk will recognize and measure the allowance for losses for financial instruments based on the ECL lifetime of the financial instrument, if the credit risk of the financial instrument has experienced a significant increase from the time of initial recognition. PT. XYZ Tbk uses information that is forward looking.